Pengaruh Kualitas Produk dan Harga Produk terhadap Keputusan Pembelian Ulang - Wakerkwa, Desina; Irmadiani, Nadia Dwi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
The objective of this study was to ascertain and elucidate the impact of product quality and product pricing on repurchasing decisions at the Singosari Semarang Branch of Waroeng Steak & Shake. This study employs explanatory research methodologies. The study included a population of 21,352 clients of Waroeng Steak and Shake Singosari Semarang. The sampling technique employed in this study was non-probability sampling, with a sample size of 100 respondents. The data gathering procedures employed in this study encompassed the utilisation of both observation and questionnaire approaches. The findings of the study indicate that product quality has a simultaneous impact on repurchase decisions. Specifically, there is a statistically significant positive relationship between product prices and repurchase decisions at the Singosari Branch of Waroeng Steak and Shake. This is supported by a Beta value of 0.652, which is positive, and a significant p-value of 0.000, indicating that the relationship is unlikely to have occurred by chance (p < 0.05). Additional findings indicate that the price of a product exerts a substantial and simultaneous impact on repurchasing decisions. Specifically, at the Singosari Branch of Waroeng Steak and Shake, there exists a positive and statistically significant relationship between product prices and repurchasing decisions. This is supported by a Beta value of 0.179, which is positive, and a significant value of 0.017, which is less than the predetermined threshold of 0.05. In order to facilitate more investigation, it is anticipated that other indicators can be identified as instruments for measuring the variables under examination, as well as the utilisation of other independent variables that possess a substantial impact on the dependent variable. For instance, by incorporating additional variables such as brand image and service quality, among others. Keywords: product quality, product price, repurchase decision